Cooperativas populares e práticas em Psicologia Social - Patricia Martins Goulart; Silvia Batista Von Borowski (Ciências Sociais Unisinos)
The main purpose of this study consisted of ascertaining the practices pursued in popu- lar cooperative arrangements within the solidarity economy, focusing on the obstacles and alternatives perceived by university extension agents. The study had an exploratory and qualitative design and examined in depth thirteen publications from 2003 to 2010, considering the field of Social Psychology. The information collected showed that self- management represents one of the main focuses of the articles analyzed. As far as the meanings attributed to work from the perspective of cooperatives are concerned, the study showed that they are connected with feelings of self-worth. Although the work in cooperatives is recognized, the cooperative members prefer formal jobs, ruled by the Consolidation of Labor Laws. This may be linked to the lack of funds and bureaucratic obstacles present in popular cooperative arrangements as well as the media’s pressure in favor of unbridled consumption and of wage labor as the main route to productive inclusion.